Pendampingan Pengembangan Soal Matematika Berkarakteristik Kemampuan Berpikir Kritis pada Guru-Guru Matematika SMP/MTs di Kecamatan Labuapi Kabupaten Lombok Barat - Arjudin Arjudin; Sripatmi Sripatmi; Sudi Prayitno; Ratna Yulis Tyaningsih; Nilza Humaira Salsabila (Pendidikan Matematika, FKIP Universitas Mataram, 2022)
This community service activity aims to increase the knowledge of Mathematics teachers of SMP/MTs in Labuapi, Lombok Barat about critical thinking skills and improve skills in developing mathematical problems characterized by critical thinking skills. This community service activity was carried out in September 2022. Community service was carried out in the form of activities consisting of (1) Focused FGD (Focus Group Discussion) increased knowledge about critical thinking skills, and (2) Workshops and assistance in developing mathematical questions characterized by critical thinking skills. This activity is expected to be useful for mathematics teachers at SMP/MTs in Labuapi and impact increasing professional competence, namely increasing knowledge about critical thinking skills and developing skills with critical thinking characteristics. The results and outputs of this community service activity are (1) positive responses from workshop participants about the usefulness of community service activities that have been carried out, (2) there is an increase in the knowledge of workshop participants about critical thinking skills and skills in developing math problems characterized by critical thinking skills, and (3) the output of mathematical questions with the characteristics of critical thinking skills developed by Mathematics teachers of SMP/MTs in Labuapi, Nusa Tenggara Barat.